Prosperity Theology and African Traditional Religion: Assessing their resonance through a case study - Court, Andrew T. (Stellenbosch Theological Journal, 2020)
Studies of Prosperity Theology in Africa have increased as research into Pentecostalism has burgeoned, but few theological analyses have explored the significance of African Traditional Religions and their role in shaping Prosperity Theology. While some studies have explored the resonance of Prosperity Theology and African Traditional Religions, they tend to do so briefly, or with a focus on sociology rather than theology. Through a case study of Nigerian Pastor Chris Oyakhilome, this research tests the thesis that many have intuited: Prosperity Theology resonates with traditional African religion, and these resonances contribute to an explanation of the expression and proliferation of Prosperity Theology in Africa. Evaluating the resonance of Oyakhilom's teaching with African Traditional Religions (relying especially on John S. Mbiti's work) demonstrates that Oyakhilom's emphasis on accessing blessing, spiritual enemies, and activating power draws heavily on the resources of the typical African religious worldview.
free